The World Needs Nuclear Power - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK There was a good deal of talk about energy at the UN General Assembly's Special Session on Sustainable Development in New York last summer, but I must tell you that , speaking for the MEA, I was alone in referring to the potential of nuclear power to help reduce green-house gas emissions. My speech was followed by that of a representative of Green peace who called for - I quote "the beginning of the phase-out of .fossil fuels and their replacement by clean renewable energy which exists in abundance. " He added: "nuclear is not an alternative..." Keywords: Nuclear power